MIMO Antenna Polynomial Weighted Average Design Method of Downward-Looking Array SAR - Hui Liu; Qing Xu; Guowang Jin; Hongmin Zhang (International Journal of Antennas and Propagation)
MIMO antenna polynomial weighted average design method of downward-looking array SAR was proposed from the angle of surveying and mapping in this paper, in order to solve the ill-posed problem that an equivalent virtual array can be implemented by a variety of physical transmitter-receiver arrays for bistatic MIMO linear array. For wave band, resolution, elevation precision, and working height concerned by the applications of surveying and mapping, the length of equivalent virtual array and actual physical array meeting the needs of large scale topographical mapping was solved. Then array numbers and position vectors of MIMO downward-looking array SAR of real aerial mapping platform were optimized. According to this design, some simulation experiments and comparisons were processed. The results proved the rationality and effectiveness of this array configuration by comparing the differences of 3D imaging results and the original simulation scene, counting mean and standard deviation of elevation reconstruction error eliminating the influence of shadow areas, and counting the probability of elevation reconstruction error within half a resolution of the whole scene and individual building area.